Penghindaran Penghindaran Pajak, Leverage dan Nilai Perusahaan: Dimoderasi oleh Transparansi - Pratami, Yolanda; Munashiroh, Hidayatul (Akuntansi & Ekonomika, 2024)
The objective of this research is to acquire empirical evidence regarding the impact of transparency on the relationship between tax avoidance and leverage in relation to a firm's value. Firm value is pivotal as it mirrors a company's performance, thereby influencing investors' perceptions. This study adopts a quantitative approach, utilizing EViews as an analytical tool to test a hypothetical model. The research specifically examines manufacturing firms listed on the Indonesia Stock Exchange during the period from 2020 to 2022. A purposive sampling technique was employed, yielding a sample size of 93 companies out of a population of 243. The empirical findings of this study indicate that tax avoidance practices can influence a company's value, whereas leverage does not. Additionally, transparency does not enhance the relationship between tax avoidance and leverage concerning firm value.